Care‐Partner Support and Hospitalization in Assisted Living During Transitional Home Health Care. Issue 5 (4th January 2021) - Wang, Jinjiao; Ying, Meiling; Temkin‐Greener, Helena; Caprio, Thomas V.; Yu, Fang; Simning, Adam; Conwell, Yeates; Li, Yue
Abstract : BACKGROUND/OBJECTIVES: Care‐partner support affects outcomes among assisted living (AL) residents. Yet, little is known about care‐partner support and its effects on hospitalization during post‐acute care transitions. This study examined the variation in care‐partner support and its impact on hospitalizations among AL residents receiving Medicare home health (HH) services. DESIGN: Analysis of national data from the Outcome and Assessment Information Set, Medicare claims, Area Health Resources File, and the Social Deprivation Index File. SETTING: AL facilities and Medicare HH agencies in the United States. PARTICIPANTS: 741, 926 Medicare HH admissions of AL residents in 2017. MEASUREMENTS: Care‐partner support during the HH admission was measured based on the type and frequency of assistance from AL staff in seven domains (i.e., activities of daily living (ADL), instrumental ADLs, medication administration, treatment, medical equipment, home safety, and transportation). Care‐partner support in each domain was measured as "assistance not needed" (reference group), "Care‐partner currently provides assistance, " "care‐partner need additional training/support to provide assistance" (i.e., inadequate care‐partner support), and "care‐partner unavailable/unlikely to provide assistance" (i.e., unavailable care‐partner support). Outcome was time‐to‐hospitalization during the HH admission. RESULTS: Among the 741, 926 Medicare HH admissions of AL residents, inadequate care‐partner support was identified for all seven domains that ranged from 13.1% (for transportation) to 49.8% (for treatment), and care‐partner support was unavailable from 0.9% (for transportation) to 11.0% (for treatment). In Cox proportional hazard models adjusted for patient covariates and geography, compared with "assistance not needed", having inadequate and unavailable care‐partner support was related to increased risk of hospitalization by 8.9% (treatment (hazard ratio (HR) =1.089, P < .001)) to 41.3% (medication administration (HR =1.413, P < .001)). CONCLUSION: For AL residents receiving HH services, having less care‐partner support was related to increased risk of hospitalization, particularly regarding medication administration, medical equipment, and transportation/advocacy.